(3JfHjg GdYbhd Ydi JfRjg GdUhajI Yf GYJbGO GdJLSje hGdYfjjI hGdGJMGO hGdMdhds - (3EHQGgje Hf MSf Hf TgGH GdOjf GdTgQGfj GdTgQRhQqj GdchQGfj, HQgGf GdOjfs
(3ChdgG (B:s
(3GdMeO ddg GdfhQ GdgGOi GdeHjf CeG HYO abO UM Yf GdfHi Udi Gddg Ydjg hSde Efg bGd (B: ( (3GdEjeGf HVY hSHYhf TYHI CaVdgG bhd dG Edg EdG Gddg hGOfGgG EeGWI GdCPi Yf GdWQjb s
(3BNQgG (B:s
(3bGd (B: (3QShd Gddg Udi Gddg Ydjg hSde(B( (3Ef ef CaVd EjeGf GdeQA Cf jYde Cf Gddg YR hLd eYg MjK cGf GfJgi(B) s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9276) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs